Photobiomodulation Therapy Decreases Oxidative Stress in the Lung Tissue after Formaldehyde Exposure: Role of Oxidant/Antioxidant Enzymes - Rodrigo Silva Macedo; Mayara Peres Leal; Tarcio Teodoro Braga; Éric Diego Barioni; Stephanie de Oliveira Duro; Anna Carolina Ratto Tempestini Horliana; Niels Olsen Saraiva Câmara; Tânia Marcourakis; Sandra Helena Poliselli Farsky; Adriana Lino-dos-Santos-Franco (Mediators of Inflammation, 2016)
Formaldehyde is ubiquitous pollutant that induces oxidative stress in the lung. Several lung diseases have been associated with oxidative stress and their control is necessary. Photobiomodulation therapy (PBMT) has been highlighted as a promissory treatment, but its mechanisms need to be better investigated. Our objective was to evaluate the effects of PBMT on the oxidative stress generated by FA exposure. Male Wistar rats were submitted to FA exposure of 1% or vehicle (3 days) and treated or not with PBMT (1 and 5 h after each FA exposure). Rats treated only with laser were used as control. Twenty-four hours after the last FA exposure, we analyzed the effects of PBMT on the generation of nitrites and hydrogen peroxide, oxidative burst, glutathione reductase, peroxidase, S-transferase enzyme activities, the gene expression of nitric oxide, cyclooxygenase, superoxide dismutase, the catalase enzyme, and heme oxygenase-1. PBMT reduced the generation of nitrites and hydrogen peroxide and increased oxidative burst in the lung cells. A decreased level of oxidant enzymes was observed which were concomitantly related to an increased level of antioxidants. This study provides new information about the antioxidant mechanisms of PBMT in the lung and might constitute an important tool for lung disease treatment.